Efficacy and Tolerability of Perampanel as Adjunctive Therapy in Chinese Patients With Focal-Onset Seizures: An Observational, Prospective Study - Zhang, Ranran; Qiao, Shan; Fang, Xiqin; Wang, Kemo; Shi, Yanting; Du, Qianwen; Yang, Tingting; Liu, Xuewu (Frontiers in Neurology, 2021)
Purpose :To evaluate the efficacy and tolerability of adjunctive perampanel(PER) in Chinese patients with focal-onset seizures, with or without secondarily generalized tonic-clonic seizures. Methods:56 patients aged 14 to 72 years were recruited consecutively in this single-center prospective observational study.All patients received PER as add-on treatment on the basis of clinical judgement.Seizure frequency , adverse events (AEs) and retention rates were obtained at 3 and 6 months after PER introduction. Results:The overall response rates were 60 % and 71.1 % after 3 and 6 months, respectively, and the freedom of seizures at the same points were reached in 8 % and 15.8 %.The retention rates were 89.3% at the 3-month follow-up and 67.9% at the 6-month follow-up. The overall incidence of adverse events was 55.4%. The leading reported AEs were dizziness (39.3%) and somnolence (25%). Conclusions:Our study confirmed the efficacy and tolerability of adjunctive PER in Chinese patients in real-life conditions. Based on our treatment experience, a lower maintenance dose of PER would be needed in Chinese patients.